Penatalaksanaan Teknik Relaksasi Lamaze dan Aromaterapi Jasmine dengan Masalah Nyeri Akut Persalinan Kala 1 Fase Aktif di Rumah Edukasi Persalinan Alami Sukoharjo - Amelia, Fena; Rahayuningsih, Tutik (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Background: Childbirth is a process of giving birth through a natural event where contractions of the mother's uterus are carried out by opening the baby. Labor pain is an unpleasant condition during the birth process which is a complex condition and has individual sensory components. The technique for reducing labor pain is done using the Lamaze relaxation technique and jasmine aromatherapy. Explaining the management of lamaze relaxation techniques and jasmine aromatherapy with the problem of acute pain in the first active phase of labor. Method: qualitative descriptive research using case studies. A total of 3 subjects were used for research who experienced acute labor pain in the first active phase. Several instruments were used to obtain data from research subjects. The sampling technique for this research uses non-probability sampling with a purposive sampling approach. Data analysis uses 4 methods, namely data collection, data reduction, data display, and conclusions. Research Results: data from three subjects stated that pain in the lower abdomen was due to uterine contractions, stabbing pain on a scale of 4-6 felt intermittently every 5 minutes for 30 seconds, facial expressions were grimacing with teeth clenched to endure the pain, occasionally moaning in pain, looks restless, seems to be holding his stomach, TTV : BP : 100/60-120/80 mmHg, N : 86-94 x/minute, RR : 20 x/minute, S : 36-37o C. Nursing Diagnosis of acute pain related to uterine contractions. The actions taken were the Lamaze relaxation technique and administering jasmine aromatherapy for 3 cycles, each cycle lasting 20 minutes. Evaluation of acute pain problems is partially resolved by lowering the pain scale from 1-3. Conclusion: Providing lamaze relaxation techniques and jasmine aromatherapy is effective in reducing labor pain.